2020
DOI: 10.1016/j.redox.2020.101714
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NRF2 by topical apocarotenoid treatment mitigates radiation-induced dermatitis

Abstract: Radiation therapy is a frontline treatment option for cancer patients; however, the effects of radiotherapy on non-tumor tissue (e.g. radiation-induced dermatitis) often worsen patient quality of life. Previous studies have implicated the importance of redox balance in preventing dermatitis, specifically in reference to modulation of the nuclear factor (erythroid-derived 2)-like 2 (NRF2) signaling pathway. Due to the cytoprotective functions of transcriptional target genes of NRF2, we investigated how modulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…However, the protein kinase mediating S40 phosphorylation remains unclear and needs further study. Taken together, these results, along with those of other studies (14,37), clearly demonstrate that Nrf2 plays a pivotal role during the process of RISI. Pharmacological induction or activation of Nrf2 has been widely studied to prevent or protect against radiation-induced dermatitis in preclinical research both in vitro and in vivo (14,37).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, the protein kinase mediating S40 phosphorylation remains unclear and needs further study. Taken together, these results, along with those of other studies (14,37), clearly demonstrate that Nrf2 plays a pivotal role during the process of RISI. Pharmacological induction or activation of Nrf2 has been widely studied to prevent or protect against radiation-induced dermatitis in preclinical research both in vitro and in vivo (14,37).…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have suggested that the antioxidant capacity of Nrf2 is mediated through ROS-eliminating enzymes, and Nrf2 is thought to protect against stress-induced cell death (13). Pharmacological induction of Nrf2 before radiation exposure is thought to prevent radiation-induced dermatitis (14). The role of Nrf2 in high-dose radiation-induced skin injury remains unknown, and there is no strong evidence that exogenous supplementation with Nrf2 is capable of attenuating RISI.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, the cytoprotective activity of bixin in keratinocytes and fibroblasts via the activation of the NRF2 pathway (master switch of the cellular antioxidant response) has been reported. 51 Here, statistically significant difference in cellular viability was observed between NC vs. V groups ( p < 0.001) and V vs. BIX 1, BIX 2, and BIX 3 groups ( p < 0.001) emphasizing the cytoprotective role of bixin in UV treated HDF cells (Fig. 2A).…”
Section: Food and Function Papermentioning
confidence: 71%
“…Most importantly, Nrf2 knockout mice showed increased numbers of neutrophils in the skin upon J o u r n a l P r e -p r o o f induction of contact dermatitis, which was a consequence of oxidative stress and enhanced chemokine production (Helou et al, 2019). They were also more sensitive to radiation-induced dermatitis (Schmidlin et al, 2020). Nrf2 is also a key regulator of the epidermal barrier, which activates a "rescue" pathway in LOR-deficient mice.…”
Section: Discussionmentioning
confidence: 99%